Chemical profiling of Honghua Xiaoyao tablet and simultaneous determination of its quality markers by liquid chromatography–tandem mass spectrometry combined with chemometrics methods. Issue 23 (20th October 2020) - Mi, Rui; Li, Xiaofeng; Zhang, Zhen; Cheng, Taofang; Tian, Saisai; Xu, Xike; Zhang, Yuhao; Yuan, Wenlin; Ye, Ji; Liu, Li; Zhang, Xinrong
Abstract: Discovering marker components of traditional Chinese medicine formulas is challenging because of the hundreds of components they inherently contain. This study first proposed a reliable and validated method for the comprehensive profiling of chemical constituents in Honghua Xiaoyao tablet by using high‐performance liquid chromatography coupled with mass spectrometry. After searching within the in‐house library, a total of 55 constituents were unambiguously characterized or tentatively identified through reference standards and by comparing mass spectrometry data with literature values. Quantitative analysis of 14 compounds, which were selected as the quality marker components based on a serum pharmacochemistry study, has been performed by triple‐quardrupole mass spectrometry technique. Multiple chemometric methods, including principal components analysis and hierarchical cluster analysis, were subsequently used to analyze the quantitative results, classify samples from three manufacturers, and distinguish the analytical markers. In method validation results, 14 quality marker compounds have shown good linearity ( R 2 ≥ 0.9965) with a relative wide concentration range and acceptable recovery at 98.39–102.46%. The proposed approach provides the chemical evidence for revealing the material basis of Honghua Xiaoyao tablet, and establishes a reliable statistical analysis‐based strategy of quality marker investigation for controlling its quality.